Overcoming the Gas–Liquid Mass Transfer of Oxygen by Coupling Photosynthetic Water Oxidation with Biocatalytic Oxyfunctionalization - Hoschek, Anna (Angew Chem Int Ed Engl, 2017)
Gas–liquid mass transfer of gaseous reactants is a major limitation for high space–time yields, especially for O(2)‐dependent (bio)catalytic reactions in aqueous solutions. Herein, oxygenic photosynthesis was used for homogeneous O(2) supply via in situ generation in the liquid phase to overcome this limitation. The phototrophic cyanobacterium Synechocystis sp. PCC6803 was engineered to synthesize the alkane monooxygenase AlkBGT from Pseudomonas putida GPo1. With light, but without external addition of O(2), the chemo‐ and regioselective hydroxylation of nonanoic acid methyl ester to ω‐hydroxynonanoic acid methyl ester was driven by O(2) generated through photosynthetic water oxidation. Photosynthesis also delivered the necessary reduction equivalents to regenerate the Fe(2+) center in AlkB for oxygen transfer to the terminal methyl group. The in situ coupling of oxygenic photosynthesis to O(2)‐transferring enzymes now enables the design of fast hydrocarbon oxyfunctionalization reactions.